Tear Rates of the Ipsilateral ACL Graft and the Contralateral Native ACL Are Similar following ACL Reconstruction - Ifran, Nadia Nastassia; Mok, Ying Ren; Krishna, Lingaraj (The Journal of Knee Surgery, 2020)
The aim of the study is to compare the tear rates of ipsilateral anterior cruciate ligament (ACL) grafts and the contralateral native ACL as well as to investigate the correlation of gender, age at time of surgery, and body mass index (BMI) with the occurrence of these injuries. The medical records of 751 patients who underwent ACL reconstruction surgery with follow-up periods of 2 to 7 years were retrospectively analyzed. Survival analyses of ipsilateral ACL grafts and contralateral native ACL were performed. Univariate and multivariate logistic regression analyses were performed to identify risk factors that were associated with these injuries. The tear rates of the ipsilateral ACL graft and contralateral ACL were 5.86 and 6.66%, respectively with no significant difference between groups (p = 0.998). The mean time of tears of the ipsilateral ACL and contralateral ACL was also similar (p = 0.977) at 2.64 and 2.78 years, respectively after surgery. Both the odds of sustaining an ipsilateral ACL graft and contralateral ACL tear were also significantly decreased by 0.10 (p = 0.003) and 0.14 (p = 0.000), respectively, for every 1-year increase in age at which the reconstruction was performed. However, graft type, gender, and BMI were not associated with an increased risk of these injuries. There was no difference between tear rates of ipsilateral ACL graft and contralateral ACL following ACL reconstruction. Patients who undergo ACL reconstruction at a young age are at an increased risk of both ipsilateral graft and contralateral ACL rupture after an ACL reconstruction. Patients who are young and more likely to return to competitive sports should be counselled of the risks and advised to not neglect the rehabilitation of the contralateral knee during the immediate and back to sports period of recovery. This is a Level III, retrospective cohort study.
Keywords: ACL tear; anterior cruciate ligament; re-injury